The Impact of Aging on Adipose Function and Adipokine Synthesis - Mancuso, Peter; Bouchard, Benjamin (Frontiers in Endocrinology, 2019)
During the last 40 years, there has been a world-wide increase in both the prevalence of obesity and an increase in the number of persons over the age of 60 due to a decline in deaths from infectious disease and the nutrition transition in low and middle income nations. While the increase in the elderly population indicates improvements in global public health, this population may experience a diminished quality of life due to the negative impacts of obesity on age-associated inflammation. Aging alters adipose tissue composition and function resulting in insulin resistance and ectopic lipid storage. A reduction in brown adipose tissue activity, declining sex hormones levels, and abdominal adipose tissue expansion occur with advancing years through the redistribution of lipids from the subcutaneous to the visceral fat compartment. These changes in adipose tissue function and distribution influence the secretion of adipose tissue derived hormones, or adipokines, that promote a chronic state of low-grade systemic inflammation. Ultimately, obesity accelerates aging by enhancing inflammation and increasing the risk of age-associated diseases. The focus of this review is the impact of aging on adipose tissue distribution and function and how these effects influence the elaboration of pro and anti-inflammatory adipokines.